Implementasi Pembelajaran Anak Berkebutuhan Khusus (ABK) di Masa Pandemi Covid 19 - Hamzah, Amir; Saputra, Agra Dwi; Handayani, Tutut; Nurlaeli (Fakultas Agama Islam Universitas Billfath, 2022)
This study aims to determine the implementation of learning for children with special needs during the COVID-19 pandemic at SLB Pembina Palembang. This type of research is descriptive qualitative. Data collection techniques using interviews, observation and documentation. Data analysis used in this research is data reduction, data presentation and conclusions. The results showed that the implementation of online learning carried out at SLB Pembina Palembang took the form of assignments, WA groups, use of zoom, alternate schools, home visits, and development of worksheets. A number of obstacles are felt by teachers and students when implementing online learning including parents cannot be actively involved, inadequate facilities, limited teachers, limited learning resources, and low student motivation